The Internalization of Hadith Values and Their Relevance to Strengthening Family Resilience in Nation Building - Wasalmi, Wasalmi; Ardiansyah, Ardiansyah; Zilsafil, Zul Ikrom; Rahman, Rahman (Islamic Management and Empowerment Journal, 2026)
Family resilience serves as a fundamental pillar of sustainable nation building. Amid contemporary social challenges such as moral decline, family disintegration, and socio-cultural transformation, the internalization of religious values becomes increasingly important. This article examines the role of Hadith values in strengthening family resilience and their contribution to nation building. Using a qualitative library research approach, the study analyzes prophetic traditions concerning family ethics, responsibility, education, justice, compassion, and moral leadership. The findings reveal that Hadith provides a comprehensive framework for developing resilient families by integrating spiritual, moral, emotional, and social dimensions. The internalization of these values fosters individuals with strong character, social responsibility, and civic awareness, thereby supporting social stability and national development. Furthermore, the prophetic model of family life extends beyond the private sphere and carries broader societal implications. The study concludes that strengthening family institutions through Hadith values is a strategic means of cultivating resilient families as the moral and social foundation of a stable and progressive nation.